The Question of Animal Experimentation - Spatzenegger, Margit (Studia Bioethica, 2016)
“I am life that wants to live, in the midst of life that wants to live” . Albert Schweitzer’s sentence outlines the ideal approach to all living beings including animals. But what to do when confronted with the so-called “life-boat situation” - save human or animal life? Such an ethical dilemma is at the heart of animal experimentation.